1993
DOI: 10.1016/0002-9378(93)90016-c
|View full text |Cite
|
Sign up to set email alerts
|

The association between prenatal stress and infant birth weight and gestational age at birth: A prospective investigation

Abstract: Independent of biomedical risk, maternal prenatal stress factors are significantly associated with infant birth weight and with gestational age at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
423
3
17

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 711 publications
(458 citation statements)
references
References 34 publications
15
423
3
17
Order By: Relevance
“…Studies have also shown that maternal stress during pregnancy can result in changes in the hypothalamic-pituitary-adrenal-axis and elevated levels of stress hormones (particularly cortisol) with premature labor, shortened pregnancy length, low-birth weight and impaired fetal brain development as a consequence ( Obel C et al 2005;Sandman CA et al 1994;Wadha PD et al 1993;Gitau R et al 1998;Copper RL et al 1996;Weinstock M 2005;Diego MA et al 2006;Field T et al 2006). In this study we did not sample salivary cortisol among the participants before and after treatment sessions which would have been interesting.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have also shown that maternal stress during pregnancy can result in changes in the hypothalamic-pituitary-adrenal-axis and elevated levels of stress hormones (particularly cortisol) with premature labor, shortened pregnancy length, low-birth weight and impaired fetal brain development as a consequence ( Obel C et al 2005;Sandman CA et al 1994;Wadha PD et al 1993;Gitau R et al 1998;Copper RL et al 1996;Weinstock M 2005;Diego MA et al 2006;Field T et al 2006). In this study we did not sample salivary cortisol among the participants before and after treatment sessions which would have been interesting.…”
Section: Discussionmentioning
confidence: 94%
“…cognitive effects in the child. Women with high antenatal anxiety or stress are more likely to have premature and low birth weight babies (Copper et al, 1996;Wadhwa et al, 1993Wadhwa et al, , 1998Field et al, 2003). Prenatal maternal stress is also suspect of affecting infant development and promoting a range of adverse temperamental effects (O'Connor et al, 2002(O'Connor et al, , 2003Field et al, 2003;Huizink et al, 2004;Laplante et al, 2004;Van den Bergh et al, 2005;Talge et al, 2007;Glover et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, common underlying factors likely influence fetal and infant growth as well as adult physiology (5). Exposure to high levels of prenatal maternal stress (PNMS) or to exogenous GCs in utero is associated not only with poor fetal growth (6)(7)(8) but also with deregulation of the hypothalamic-pituitary-adrenal axis (9), which is involved in metabolic pathways (10) and likely represents a mediating mechanism in the developmental origins of adult diseases (2,3,11,12).…”
mentioning
confidence: 99%